2000
DOI: 10.1017/s0140525x00422417
|View full text |Cite
|
Sign up to set email alerts
|

Niche construction: A pervasive force in evolution?

Abstract: Abstract:We propose a conceptual model that maps the causal pathways relating biological evolution to cultural change. It builds on conventional evolutionary theory by placing emphasis on the capacity of organisms to modify sources of natural selection in their environment (niche construction) and by broadening the evolutionary dynamic to incorporate ontogenetic and cultural processes. In this model, phenotypes have a much more active role in evolution than generally conceived. This sheds light on hominid evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…6. It is important to note that there has been quite some discussion on the definition of niche construction (e.g., Godfrey-Smith, 2000;Laland et al, 2000;Reed, 1996;van der Steen, 2000). Some authors found the choice of the term "construction" unfortunate; others have argued that relocating to a different place does not count as niche construction.…”
Section: Statedmentioning
confidence: 99%
“…6. It is important to note that there has been quite some discussion on the definition of niche construction (e.g., Godfrey-Smith, 2000;Laland et al, 2000;Reed, 1996;van der Steen, 2000). Some authors found the choice of the term "construction" unfortunate; others have argued that relocating to a different place does not count as niche construction.…”
Section: Statedmentioning
confidence: 99%